Diffusivity of Point Defects in the Passive Film on Stainless Steel - A. Fattah-alhosseini; M. H. Alemi; S. Banaei (International Journal of Electrochemistry)
The semiconductor properties of passive films formed on AISI 316 stainless steel in sulfuric acid solution were studied by employing Mott-Schottky analysis in conjunction with the point defect model. The donor density of the passive films, which can be estimated by the Mott-Schottky plots, changes depending on the film formation potentials. Based on the Mott-Schottky analysis, an exponential relationship between donor density and the film formation potentials of the passive films was developed. The results showed that the donor densities evaluated from Mott-Schottky plots are in the range 2-3 × 1021 cm−3 and decreased with the film formation potential. By assuming that the donors are oxygen ion vacancies and/or cation interstitials, the diffusion coefficient of the donors, (𝐷𝑂), is calculated to be approximately 3.12 × 10−16 cm2/s.